HUBUNGAN TINGKAT PENGETAHUAN DAN KETERPAPARAN MEDIA MASSA DENGAN PERILAKU SEKSUAL REMAJA DI SMA NEGERI 1 PARIAMAN - Anggraini, Marisa Lia; Wahyuningsih, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
At this time, many problems occur among teenagers, one of which is sexual behavior. The report from the Indonesian Child Protection Commission (KPAI) West Sumatra in 2019 contained 107 cases of sexual behavior. Factors that can trigger sexual behavior among adolescents are such as knowledge and exposure to mass media. The purpose of this study was to determine the relationship between knowledge level and mass media exposure with adolescent sexual behavior at SMA Negeri 1 Pariaman. This type of research is descriptive analytic with a cross sectional research design. The study was conducted in May - June 2022. The population in this study were all students of class X at SMA 1 Pariaman in 2022 (10 Local) as many as 328 people, the number of samples in this study was 77 people with simple random sampling technique. Data were analyzed by univariate and bivariate analysis using Chi-Square test. The results of the study were 29 people (37.2%) of respondents who carried out deviant sexual behavior, 28 people (36.4%) of respondents who had a sufficient level of knowledge about sexual behavior and 28 people (36.4%) of respondents who were exposed to mass media in the category heavy. The results of statistical tests showed that there was a relationship between the level of knowledge (p value = 0.002 and exposure to mass media (p value = 0.004) with sexual behavior in adolescents. The conclusion was that there was a relationship between knowledge and exposure to mass media with sexual behavior in adolescents. It is recommended for adolescents to use access Mass media in the positive category only means not accessing things or content related to pornographic media.Keywords: Knowledge, Mass Media Exposure, Sexual Behavior